Avaliação temporal do acúmulo de fitomassa e trocas gasosas do capim-canarana em função da salinidade da água de irrigação - Morais Neto, Luiz Barreto de (2009)
This study was conducted to evaluate the effect of saline irrigation water and different cut times on the components of biomass, gas exchange, growth and yield of canarana grass (Echinochloa pyramidalis). The seedlings were planted in plastic pots with a volume of 8 L containing soil type QUARTZARENIC NEOSOL sandy texture, under conditions of a greenhouse. For the experiment in which we evaluated the components of biomass, the experimental design was completely casualized sub divided plots, the salinity levels (0.75, 2.0, 4.0, 6.0 and 8.0 dS m-1) in the main plots and harvest age (21, 28, 35, 42 and 49 days) in the plot, with five replicates and the experiment was evaluated gas exchange, growth and production, randomized design, in a 5 x 5, consists of cutting ages (21, 28, 35, 42 and 49 days) and five doses saline water (0.75, 2.0, 4.0, 6.0 and 8.0 dS/m) with five replications. After the cut for uniformity, 56 days after the planting began the treatments. Upon reaching the age cutoff determined, the plants were cut and then the material collected was fractionated into leaves, stems and dead material. It was determined the mass of dry total forrage, dry matter of forage dead, dry mass of live forrage, dry matter of green blade, dry mass of green stem, material relationship alive matter/dead material and leaf/stem. Salinity affected the photosynthetic rates and transpiration rates, but did not affect stomatal conductance. There was tolerance to salt stress in each section. There was no interaction between the factors studied. Salinity reduced the dry mass of total herbage, dry forrage of green, dry blade green and dry mass of stem green. There was no effect of salinity on dry mass of dead forrage, live material for dead plant material and leaf/stem. The salinity changed the partition of dry matter, reducing the percentage of stems and increasing the proportion of leaves in the dry mass of total forrage. The increase of the cut caused increases in dry mass of total forrage, dead forrage, live forrage, green stems and green leaves. From the cutting age of 28 days of dry forrage dead had increased quite markedly. The increase in dry weight of stems was accentuated after 35 days. The extension of the cut caused a decline in relations material living dead plant material and leaf/stem. Salinity affected the photosynthetic rates and transpiration, but did not affect stomatal conductance. Climatic variations in the different days on which the measurements were made of gas exchange, caused differences in photosynthetic rate, transpiration rate and stomatal conductance. Climatic variations in the different days on which the measurements were made of gas exchange, caused differences in photosynthetic rate, transpiration rate and stomatal conductance. Salinity did not cause variations in specific leaf area, leaf weight and leaf area ratio, but these three variables decreased with increasing age. The tolerance to salt stress decreased with advancing age. This species was moderately tolerant to higher salinity level and longer exposure to stress. The canarana grass can be irrigated with water electrical conductivity of up to 2.0 dS/m. Cutting canarana grass should be done at 21 days